2018
DOI: 10.1200/jco.2017.76.6840
|View full text |Cite|
|
Sign up to set email alerts
|

Venetoclax for Patients With Chronic Lymphocytic Leukemia With 17p Deletion: Results From the Full Population of a Phase II Pivotal Trial

Abstract: Purpose Venetoclax is an orally bioavailable B-cell lymphoma 2 inhibitor. US Food and Drug Administration and European Medicines Agency approval for patients with 17p deleted relapsed/refractory chronic lymphocytic leukemia [del(17p) CLL] was based on results from 107 patients. An additional 51 patients were enrolled in a safety expansion cohort. Extended analysis of all enrolled patients, including the effect of minimal residual disease (MRD) negativity on outcome, is now reported. Patients and Methods Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
217
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(230 citation statements)
references
References 11 publications
2
217
0
11
Order By: Relevance
“…Interestingly, reflecting pre-clinical data showing a TP53-independent induced apoptosis of CLL cells [11], venetoclax then showed a potent activity in high-risk CLL harboring a 17p deletion in a phase II study [12], leading to US Food and Drug Agency (FDA) approval in this setting in 2016. The updated results of this study [13] showed an overall response rate (ORR) of 77% and minimal residual disease (MRD) negativity of 30% with a sensitivity of 10 −4 , in a population of CLL patients with 17p deletion, mostly in the relapse setting.…”
Section: Clinical Activity Of Venetoclax In Chronic Lymphocytic Leukemiamentioning
confidence: 86%
“…Interestingly, reflecting pre-clinical data showing a TP53-independent induced apoptosis of CLL cells [11], venetoclax then showed a potent activity in high-risk CLL harboring a 17p deletion in a phase II study [12], leading to US Food and Drug Agency (FDA) approval in this setting in 2016. The updated results of this study [13] showed an overall response rate (ORR) of 77% and minimal residual disease (MRD) negativity of 30% with a sensitivity of 10 −4 , in a population of CLL patients with 17p deletion, mostly in the relapse setting.…”
Section: Clinical Activity Of Venetoclax In Chronic Lymphocytic Leukemiamentioning
confidence: 86%
“…Because of the striking improvement in clinical outcomes among patients with del17p using ibrutinib and venetoclax, we expect that CLL FISH testing will continue to increase in the future. 20, 21 …”
Section: Discussionmentioning
confidence: 99%
“…Because of the striking improvements in clinical outcomes noted among patients with del17p treated with ibrutinib and venetoclax, we expect that FISH testing for CLL will continue to increase in the future. 20,21 In contrast, IgV H mutation analysis has remained prognostic and has not been incorporated into guideline treatment algorithms since 2009. Now that FCR also has been found to demonstrate a progression-free survival of >10 years in a sizeable percentage of patients with mutated IgV H status, 22,23 there may be an increase in the use of this test in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Venetoclax (ABT-199/GDC-0199) is a potent, selective B-cell lymphoma-2 (BCL-2) inhibitor 8 that was first indicated for the treatment of patients with chronic lymphocytic leukemia (CLL) who have received at least one prior therapy. 9,10 Venetoclax demonstrated modest single-agent activity in patients with relapsed or refractory AML 11 and synergistic activity with HMAs and LDAC in preclinical models of AML. 12 These findings prompted evaluation of venetoclax in combination with an HMA (azacitidine or decitabine; NCT02203773) or LDAC (NCT02287233) in patients 65 years of age or older newly diagnosed with AML and not eligible for standard induction therapy.…”
Section: Introductionmentioning
confidence: 99%